The different release techniques in high level archery: A comparative case study - Deniz Sımsek; Hayri Ertan (Türk Spor ve Egzersiz Dergisi)
The muscle-contraction strategy between the predominant forearm and pull finger used in archery is defined as a response to the fall of the "clicker" by active contraction of the m. extensor digitorum (MED) and the gradual relaxation of the m. flexor digitorum superficialis (MFDS). However, there are no studies regarding whether different finger placement techniques on the bowstring have an effect on proper balance between the forearm flexor/extensor muscles. This different hook strategy (upper two fingers, lower two fingers, and three finger hook) may affect isometric contraction before the snap of the clicker, which is thought to have positive effects on archer performance (muscle activation and balance). The purpose of this study is to make a more detailed analysis of the different hook strategy performed by a particular top-level archer and to consider the advantages this strategy may have on bowstring behavior after release. A high-level archer (FITA scores gt; 1300) volunteered to participate in this study. The subject engaged in a single test session consisting of six shots. The electromyography (EMG) activity of the drawing arm muscle was quantified. The finger hook has affected isometric contraction before the snap of the clicker and caused sudden contraction of extensor, gradually relaxation of flexor muscles. The study results found that this three finger hook strategy can be used in the drawing arm with success, as it may avoid causing a lateral deflection of the bowstring.